Spirituality in Coping with Infertility Stigma: A Mixed Method Study - Houndebasso-Ahoga, Jocelyne A.; Wambugu, Anne Gathoni; Makena, Veronica Kaari (European Scientific Journal, ESJ, 2026)
Spirituality and religion are often involved in the coping approaches of women facing the psychosocial challenge of infertility in several African cultures. This convergent mixed-methods study examined spirituality in coping with infertility-related stigma among 384 women attending evangelical churches in Zou County, Benin Republic. Data were collected using standardized instruments, the Assessment of Spirituality and Religious Sentiments (ASPIRES) and the COMPI Coping Strategy Scale (CSS), supplemented by focus groups and interviews with 45 church leaders. Quantitative data analysis was done with SPSS version 25.0, and a matched mixed-method approach was used for the qualitative data analysis. In terms of results, about spirituality, the Spiritual Transcendence scale was dominated by the Prayer Fulfilment subscale, and integration of qualitative findings confirmed a prayer-centred spirituality among surveyed women. For coping strategies, the frequency of use presented as respectively, active-confronting, meaning-based, passive-avoidance, and active-avoidance. In addition, the qualitative data revealed a three-stage coping trajectory: early-stage avoidance and shame; middle-stage indifference and adaptation; and late-stage meaning-based acceptance. Regarding spirituality in coping with infertility stigma, Spiritual Transcendence significantly predicted Coping Strategies, accounting for 20.3% of variance. In line with the massive prevalence of prayer in the women’s management of infertility stigma, the important remaining unexplained variance suggests that spirituality is much more a coping resource than a discrete strategy. The study contributes to understanding culturally situated coping mechanisms and informs interventions for mental health support in religious communities. Implications for clinical practice and church-based counselling are discussed.